2021
DOI: 10.1101/2021.03.06.21253050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of HIV and Mycobacterium tuberculosis among University Students in Port Harcourt, Nigeria

Abstract: Assessment of HIV and Mycobacterium tuberculosis infection is crucial to detect HIV and Mycobacterium tuberculosis coinfection and the strategy for infection management and treatment. This study assessed the proportion of students with HIV, Mycobacterium tuberculosis, and HIV and Mycobacterium tuberculosis coinfection. Two hundred and thirty five university students in Port Harcourt, Nigeria were recruited, ages 16 to 39 years. Samples of blood were collected and processed using standard laboratory procedures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
1
1
Order By: Relevance
“…The association was, however, not statistically significant (p = 0.252). There is nonstatistical association between this study and a study in Port Harcourt Nigeria which showed that females had higher TB (2.3%) than males (1.7%) and sex was the main correlate (P<0.05) of TB [39]. For the association between HIV and tuberculosis, the prevalence of tuberculosis among presumptive TB patients with HIV was 29.6%.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The association was, however, not statistically significant (p = 0.252). There is nonstatistical association between this study and a study in Port Harcourt Nigeria which showed that females had higher TB (2.3%) than males (1.7%) and sex was the main correlate (P<0.05) of TB [39]. For the association between HIV and tuberculosis, the prevalence of tuberculosis among presumptive TB patients with HIV was 29.6%.…”
Section: Discussioncontrasting
confidence: 57%
“…The finding from this study is dissimilar to findings from studies including in Benue state Nigeria which showed that the prevalence of TB significantly (χ 2 = 8.458; P = 0.003) highest in the 15-34 years age group (22.0%) compared to other age groups [26]. Also, in Port Harcourt Nigeria, the age-specific infection rate had a higher Tb in the age group >25 years (2.8%) than in <25 years (2.3%) and Age was the main correlate (P<0.05) of TB [39]. The possible reason for the dissimilar findings between this study and other studies may be due to variation in study populations between the studies.…”
Section: Discussionmentioning
confidence: 86%